Unveiling the Moderating Role of Psychological Contract Breach in the Relationship Between Psychological Empowerment and Work Engagement - Monje-Amor, Ariadna (Journal of Tourism, Sustainability and Well-being, 2025)
This study investigated the moderating role of psychological contract breach on the relationship between psychological empowerment and work engagement among employees in the tourism and hospitality industries in Galicia, northwest Spain. Employing a quantitative approach, the research gathered data from 378 employees, with quantitative data analysed using regression analyses in SPSS. Additionally, the questionnaire included several open questions, providing supplementary qualitative insights, which were analysed thematically. The findings indicate a significant moderating effect of psychological contract breach on the psychological empowerment-work engagement relationship, particularly pronounced among employees experiencing high levels of contract breach. Five main themes emerged, explaining why employees perceive psychological contract breach. The study highlights the critical role of psychological contract breach in influencing the dynamics between psychological empowerment and work engagement. This is the first study to explore these connections, providing new insights into the psychological mechanisms involved. The results can inform strategies to improve employee well-being and organisational effectiveness in the tourism and hospitality sectors. Several practical implications for organisations and policymakers are presented.